SAT1000 - P925

Geometry Level 4

Given that: cos 10 α = a 1 cos 10 α + a 2 cos 8 α + a 3 cos 6 α + a 4 cos 4 α + a 5 cos 2 α + a 6 \cos 10\alpha = a_1 \cos^{10} \alpha + a_2 \cos^8 \alpha + a_3 \cos^6 \alpha + a_4 \cos^4 \alpha + a_5 \cos^2 \alpha + a_6

Then find a 1 a 4 + a 5 a_1-a_4+a_5 .


Have a look at my problem set: SAT 1000 problems


The answer is 962.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

David Vreken
Jul 12, 2020

By De Moivre's Theorem and then binomial expansion,

cos 5 x + i sin 5 x \cos 5x + i \sin 5x

= ( cos x + i sin x ) 5 = (\cos x + i \sin x)^{5}

= ( 5 0 ) ( cos x ) 5 ( i sin x ) 0 + ( 5 1 ) ( cos x ) 4 ( i sin x ) 1 + ( 5 2 ) ( cos x ) 3 ( i sin x ) 2 + ( 5 3 ) ( cos x ) 2 ( i sin x ) 3 + ( 5 4 ) ( cos x ) 1 ( i sin x ) 4 + ( 5 5 ) ( cos x ) 0 ( i sin x ) 5 = {5 \choose 0} (\cos x)^{5} (i \sin x)^{0} + {5 \choose 1} (\cos x)^{4} (i \sin x)^{1} + {5 \choose 2} (\cos x)^{3} (i \sin x)^{2} + {5 \choose 3} (\cos x)^{2} (i \sin x)^{3} + {5 \choose 4} (\cos x)^{1} (i \sin x)^{4} + {5 \choose 5} (\cos x)^{0} (i \sin x)^{5}

= cos 5 x + 5 i cos 4 x sin x 10 cos 3 x sin 2 x 10 i cos 2 x sin 3 x + 5 cos x sin 4 x + i sin 5 x = \cos^5 x + 5i \cos^4 x \sin x - 10 \cos^3 x \sin^2 x - 10i \cos^2 x \sin^3 x + 5 \cos x \sin^4 x + i \sin^5 x

Equating real parts and then using the identity sin 2 x = 1 cos 2 x \sin^2 x = 1 - \cos^2 x ,

cos 5 x \cos 5x

= cos 5 x 10 cos 3 x sin 2 x + 5 cos x sin 4 x = \cos^5 x - 10 \cos^3 x \sin^2 x + 5 \cos x \sin^4 x

= cos 5 x 10 cos 3 x ( 1 cos 2 x ) + 5 cos x ( ( 1 cos 2 x ) ) 2 = \cos^5 x - 10 \cos^3 x (1 - \cos^2 x) + 5 \cos x ((1 - \cos^2 x))^2

= 16 cos 5 x 20 cos 3 x + 5 cos x = 16\cos^5 x - 20 \cos^3 x + 5 \cos x

Using the double angle formula cos 2 α = 2 cos 2 α 1 \cos 2\alpha = 2\cos^2 \alpha - 1 ,

cos 10 x \cos 10x

= cos 2 ( 5 x ) = \cos 2(5x)

= 2 cos 2 5 x 1 = 2\cos^2 5x - 1

= 2 ( 16 cos 5 x 20 cos 3 x + 5 cos x ) 2 1 = 2(16\cos^5 x - 20 \cos^3 x + 5 \cos x)^2 - 1

= 512 cos 10 x 1280 cos 8 x + 1120 cos 6 x 400 cos 4 x + 50 cos 2 x 1 = 512 \cos^{10} x - 1280 \cos^{8} x + 1120 \cos^{6} x - 400 \cos^{4} x + 50 \cos^{2} x - 1

Therefore, a 1 = 512 a_1 = 512 , a 4 = 400 a_4 = -400 , a 5 = 50 a_5 = 50 , and a 1 a 4 + a 5 = 962 a_1 - a_4 + a_5 = \boxed{962} .

All expressions cos n x \cos{nx} are related to T n ( cos x ) = cos n x T_{n}(\cos{x}) = \cos{nx} , the n n th Chebyshev Polynomial of the First Kind. Here is a fabulous Brilliant article about these functions.

Importantly Chebyshev polynomials have the recurrence relation T n + 1 ( x ) = 2 x T n ( x ) T n 1 ( x ) T_{n+1}(x) = 2x T_{n}(x) - T_{n - 1}(x) where T 0 ( x ) = 1 T_{0}(x) = 1 and T 1 ( x ) = x T_{1}(x) = x . Therefore, T 10 ( x ) = 512 x 10 1280 x 8 + 1120 x 6 400 x 4 + 50 x 2 1 T_{10}(x) = 512x^{10} - 1280x^8 + 1120x^6 - 400x^4 + 50x^2 - 1 . Thus, a 1 = 512 , a 4 = 400 , a 5 = 50 a_1 = 512, a_4 = -400, a_5 = 50 and a 1 a 4 + a 5 = 962 a_1 - a_4 + a_5 = \boxed{962} .

a 1 = 512 , a 4 = 400 , a 5 = 50 a 1 a 4 + a 5 = 962 a_1=512,a_4=-400,a_5=50\implies a_1-a_4+a_5=\boxed {962} .

Got a proof?

Pi Han Goh - 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...